Dietary patterns of patients with psoriasis at a public healthcare institution in Brazil - Figueira Polo, Tatiana Cristina [UNESP]; Corrente, Jose Eduardo [UNESP]; Bartoli Miot, Luciane Donida [UNESP]; Papini, Silvia Justina [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2020)
Background: Psoriasis is a chronic inflammatory disease with systemic repercussions and an association with comorbidities such as metabolic syndrome, cardiovascular diseases, and obesity. Psoriasis patients have a higher prevalence of obesity compared to the general population. Diet is a relevant environmental factor, since malnutrition, inadequate body weight, and metabolic diseases, in addition to the direct health risk, impair the treatment of psoriasis. Objectives: To evaluate food intake patterns, anthropometric, and metabolic syndrome-related aspects in psoriasis patients. Methods: Cross-sectional study through anthropometric assessment and food frequency questionnaire. Food frequency questionnaire items were evaluated by exploratory factor analysis and identified dietary patterns were analyzed by multivariate methods. Results: This study evaluated 94 patients, 57% female, with a mean age of 54.9 years; the prevalence of obesity was 48% and of metabolic syndrome, 50%. Factor analysis of the food frequency questionnaire identified two dietary patterns: Pattern 1 - predominance of processed foods; Pattern 2 - predominance of fresh foods. Multivariate analysis revealed that Patterns 1 and 2 showed inverse behaviors, and greater adherence to Pattern 2 was associated with females, eutrophic individuals, absence of lipid and blood pressure alterations, and lower waistto-hip ratio and skin disease activity. Study limitations: Monocentric study conducted at a public institution, dependent on dietary memory. Conclusion: Two dietary patterns were identified in a Brazilian sample of psoriasis patients. The prevalence of obesity and metabolic syndrome were greater than in the adult Brazilian population. The fresh diet was associated with lower indicators of metabolic syndrome in this sample. (C) 2020 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Feeding behavior; Food consumption; Psoriasis